HPLC-DAD profiles and pharmacological insights of Onobrychis argyrea subsp isaurica extracts. (October 2018) - Guler, Gokalp Ozmen; Zengin, Gokhan; Karadag, Firat; Mollica, Adriano; Picot, Carene Marie Nancy; Mahomoodally, Mohamad Fawzi
Graphical abstract: Highlights: Pharmacological properties of Onobrychis argyrea subsp isaurica were explained. Antioxidant abilities were detected by different assays. Enzyme inhibitory effects were investigated against key enzymes. Computational approaches were performed to understand phenolic-enzyme interactions. O. argyrea subsp. isaurica may be a potential source of biologically-active compounds. Abstract: Onobrychis argyrea Boiss. subsp. Isaurica (Fabaceae), endemic to the eastern Mediterranean region, is a poorly studied medicinal plant. This study sets out to investigate into antioxidant and inhibitory activities of O. argyrea extracts (ethyl acetate, methanol, and water) against key enzymes linked to diabetes (α-amylase, α-glucosidase), Alzheimer's disease (acetylcholinesterase, butyrylcholinesterase), and skin hyperpigmentation (tyrosinase). Phytochemical composition was determined by HPLC-DAD and in silico approach used to provide additional insight of the possible interaction of the identified phenolic compounds with the studied enzymes. The methanol extract showed potent inhibitory action against acetylcholinesterase (1.55 mg GALAE/g extract), tyrosinase (61.61 mg KAE/g extract), and glucosidase (20.17 mmol ACAE/g extract). The methanol extract of O. argyrea exhibited potent radical scavenging potential (126.51 mg TE/g extract for DPPH scavenging assay) and reducing capacities (311.36 and 200.70 mg TE/g extract, for CUPRAC and FRAP assays, respectively). Quercetin, apigenin, and benzoic acid were identified in significant amounts in the methanol extract of O. argyrea . Quercetin interacted with the catalytic pocket of glucosidase by establishing hydrogen bonds with Ser157, Ser241, Asp307, and π-π interactions with His280 and Tyr158. The observed inhibitory effects of O. argyrea extracts on the studied enzyme suggest that this plant could be a promising source of naturally occurring chemical compounds for the management of diabetes, Alzheimer's disease, skin hyperpigmentation disorders, as well as, oxidative stress-related complications.